Low-temperature structural effects in the (TMTSF)2PF6 and AsF6 Bechgaard salts - Foury-Leylekian, P.; Petit, S.; Mirebeau, I.; André, G.; De Souza, M. [UNESP]; Lang, M.; Ressouche, E.; Moradpour, A.; Pouget, J. P. (American Physical Society (APS), 2013)
We present a detailed low-temperature investigation of the statics and dynamics of the anions and methyl groups in the organic conductors (TMTSF) 2PF6 and (TMTSF)2AsF6 (TMTSF: tetramethyl-tetraselenafulvalene). The 4 K neutron-scattering structure refinement of the fully deuterated (TMTSF)2PF6-D12 salt allows locating precisely the methyl groups at 4 K. This structure is compared to the one of the fully hydrogenated (TMTSF)2PF6-H12 salt previously determined at the same temperature. Surprisingly, it is found that deuteration corresponds to the application of a negative pressure of 5×102 MPa to the H12 salt. Accurate measurements of the Bragg intensity show anomalous thermal variations at low temperature both in the deuterated PF 6 and AsF6 salts. Two different thermal behaviors have been distinguished. Small Bragg-angle measurements reflect the presence of low-frequency modes at characteristic energies θE = 8.3 K and θE = 6.7 K for the PF6-D12 and AsF6-D12 salts, respectively. These modes correspond to the low-temperature methyl group motion. Large Bragg-angle measurements evidence an unexpected structural change around 55 K, which probably corresponds to the linkage of the anions to the methyl groups via the formation of F...D-CD2 bonds observed in the 4 K structural refinement. Finally we show that the thermal expansion coefficient of (TMTSF)2PF6 is dominated by the librational motion of the PF6 units. We quantitatively analyze the low-temperature variation of the lattice expansion via the contribution of Einstein oscillators, which allows us to determine for the first time the characteristic frequency of the PF6 librations: θE ≈ 50 K and θE = 76 K for the PF6-D12 and PF6-H12 salts, respectively. © 2013 American Physical Society.